If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4x = -1 + 2x Solving 9 + 4x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 4x + -2x = -1 + 2x + -2x Combine like terms: 4x + -2x = 2x 9 + 2x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 2x = -1 + 0 9 + 2x = -1 Add '-9' to each side of the equation. 9 + -9 + 2x = -1 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = -1 + -9 2x = -1 + -9 Combine like terms: -1 + -9 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 2bx-box=-8 | | 12/25m=9/50 | | 5x+100+2=2x+1 | | 1.2x=2.76 | | 5x+7=2x+2 | | 3x+12=180-7x+32 | | 8-t=t | | -24=1a-15 | | h+9=8(k-7) | | V/8=19 | | 7X-13=5X+21 | | 8x^24+10x^16+5x+18=0 | | w+15=-3 | | 9x+72+2=7x+64 | | y=5y-35 | | -42+p=7 | | N+6n=-21 | | 6y*4= | | t-(-8)=16 | | x+8-6x=-7 | | 9y^4+4x^2=0 | | 3+X/7 | | 12=a+5bfora | | [b+5]=1 | | 20w^2+8w=0 | | (15-2x)*(x+7)=38 | | (x-7)(2x-6)=0 | | W=6/7(u+6v) | | 12x+21=-2x-21 | | 6=-5-x | | 3(n-1)=-5n+3-2n | | 5.21=10 |